Vaccination against Anthrax with Attenuated Recombinant Strains of Bacillus anthracis That Produce Protective Antigen - Barnard, John P. (American Society for Microbiology, 1999)
The protective efficacy of several live, recombinant anthrax vaccines given in a single-dose regimen was assessed with Hartley guinea pigs. These live vaccines were created by transforming ΔANR and ΔSterne, two nonencapsulated, nontoxinogenic strains of Bacillus anthracis, with four different recombinant plasmids that express the anthrax protective antigen (PA) protein to various degrees. This enabled us to assess the effect of the chromosomal background of the strain, as well as the amount of PA produced, on protective efficacy. There were no significant strain-related effects on PA production in vitro, plasmid stability in vivo, survival of the immunizing strain in the host, or protective efficacy of the immunizing infection. The protective efficacy of the live, recombinant anthrax vaccine strains correlated with the anti-PA antibody titers they elicited in vivo and the level of PA they produced in vitro.